Analisis Peran Pemerintah Daerah dalam Menigkatkan Kualitas Sumber Daya Manusia Lokal : Studi Kasus Program Beasiswa Pendidikan Tinggi di Kabupaten Bojonegoro - Safina Rahma Isro’in Maftukha; Muhammad Farid Ma’ruf; Galih Wahyu Pradana; Deby Febrian Eprilianto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Human resource quality serves as a crucial pillar for national development, as it significantly influences a country’s progress and competitiveness. Therefore, enhancing human resource capacity has become a strategic priority, particularly at the regional level where local governments play a vital role. The Government of Bojonegoro Regency has introduced several initiatives to support this objective, including the Ten Scholars per Village Scholarship Program, the Scientist Scholarship, and Final Project Assistance. Despite these efforts, several implementation challenges remain, such as cases of manipulated eligibility requirements among applicants, the absence of a digitized system for registration and document submission, and limited communication channels between program administrators and scholarship recipients. This research seeks to examine, explain, and evaluate the role of local government, especially the Education Office, in executing scholarship programs based on the theoretical framework of government roles as regulator, dynamizer, and facilitator. The study employs a descriptive qualitative method, utilizing observation, interviews, and documentation for data collection, followed by data analysis using the Miles and Huberman model. The findings reveal that although the local government has begun implementing scholarship programs, the execution is not fully effective. Supervision during participant selection focuses mainly on administrative completeness rather than document authenticity. Furthermore, direct outreach activities are limited to certain regions, coordination with village authorities remains minimal, and digital transformation has yet to be realized due to unsuccessful collaboration with the Communication and Information Agency despite several coordination meetings.